An exploratory survey of transfer pricing in selected South African listed companies - A. A.P.C. Geboers; E. O. Uliana; P. B. Dugmore (South African Journal of Business Management, 1989)
The use of transfer pricing among certain sectors of the JSE is investigated by means of a questionnaire survey. Information regarding the transfer pricing methods used and the management control systems applicable to those prices was requested. Where appropriate, comparison with similar studies carried out in other countries was made. Findings are largely in keeping with the position generally suggested by the literature. However, one particularly interesting difference between this study and comparable surveys carried out overseas is that in South Africa the minimization of tax is ranked relatively lower as an objective of the transfer pricing system. Another notable finding is that while transfer pricing among the companies that indicated they were using it, appears to be at a sophisticated level, a large proportion of the companies surveyed indicated that they did not use transfer pricing even though they could have been expected to be operating on a decentralized basis.
Keywords: 650